A novel function of the key nitrogen-fixation activator NifA in beta-rhizobia: Repression of bacterial auxin synthesis during symbiosis - Bellés-Sancho, Paula; Liu, Yilei; Heiniger, Benjamin; von Salis, Elia; Eberl, Leo; Ahrens, Christian H.; Zamboni, Nicola; Bailly, Aurélien; Pessi, Gabriella (Frontiers in Plant Science, 2022)
Rhizobia fix nitrogen within root nodules of host plants where nitrogenase expression is strictly controlled by its key regulator NifA. We recently discovered that in nodules infected by the beta-rhizobial strain Paraburkholderia phymatum STM815, NifA controls expression of two bacterial auxin synthesis genes. Both the iaaM and iaaH transcripts, as well as the metabolites indole-acetamide (IAM) and indole-3-acetic acid (IAA) showed increased abundance in nodules occupied by a nifA mutant compared to wild-type nodules. Here, we document the structural changes that a P. phymatum nifA mutant induces in common bean (Phaseolus vulgaris) nodules, eventually leading to hypernodulation. To investigate the role of the P. phymatum iaaMH genes during symbiosis, we monitored their expression in presence and absence of NifA over different stages of the symbiosis. The iaaMH genes were found to be under negative control of NifA in all symbiotic stages. While a P. phymatum iaaMH mutant produced the same number of nodules and nitrogenase activity as the wild-type strain, the nifA mutant produced more nodules than the wild-type that clustered into regularly-patterned root zones. Mutation of the iaaMH genes in a nifA mutant background reduced the presence of these nodule clusters on the root. We further show that the P. phymatum iaaMH genes are located in a region of the symbiotic plasmid with a significantly lower GC content and exhibit high similarity to two genes of the IAM pathway often used by bacterial phytopathogens to deploy IAA as a virulence factor. Overall, our data suggest that the increased abundance of rhizobial auxin in the non-fixing nifA mutant strain enables greater root infection rates and a role for bacterial auxin production in the control of early stage symbiotic interactions.